Entertainment-Education Campaigns and COVID-19: How Three Global Organizations Adapted the Health Communication Strategy for Pandemic Response and Takeaways for the Future. Issue 1 (2nd January 2021) - Riley, Amy Henderson; Sangalang, Angeline; Critchlow, Elizabeth; Brown, Neemesha; Mitra, Radharani; Campos Nesme, Brenda
ABSTRACT: COVID-19 created a substantial set of challenges for health communication practitioners in the process of planning, implementing, and evaluating entertainment-education (EE) campaigns. EE is a theory and evidence-based communication strategy that employs entertainment media for educational messaging. Here, we briefly review EE campaigns in response to previous health emergencies and present three cases of EE responses to the COVID-19 pandemic from leading global organizations (PCI Media, BBC Media Action, and Sesame Workshop). Responses ranged from adaptation and re-distribution of existing content to creating new content under social-distancing restrictions and utilizing transmedia. These cases demonstrate that EE initiatives responding to future pandemics may be well served by starting with existing infrastructure to quickly build capacity, support, and trust; working with partners to tailor programs to the local context; and continuing to focus on good storytelling while simultaneously considering evolving media formats and theory.